2019
DOI: 10.3389/fimmu.2019.00567
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Immunization With an RSV G Glycoprotein Fragment Primes IL-17-Mediated Immunopathology Upon Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of serious respiratory tract disease but there is no licensed RSV vaccine. Immunopathological mechanisms have long been suspected as operating in the development of severe RSV disease and have hampered the development of safe and effective vaccines. Here, we show that unlike intranasal immunization, sublingual immunization with RSV glycoprotein fragment containing the central conserved region (Gcf) primes the host for severe disease upon RSV challenge. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Wang et al, 2016). IL-17A is also there is no vaccine available against RSV and its precise mechanism of pathogenesis is not fully explored (Cheon et al, 2019). Upregulation of Th17 cells and IL-17A responses in RSV infection are associated with increased neutrophil recruitment and pulmonary pathogenesis in infants as well as in BALB/c mouse model of RSV (Mukherjee et al, 2011).…”
Section: Influenza Virusmentioning
confidence: 99%
“…Wang et al, 2016). IL-17A is also there is no vaccine available against RSV and its precise mechanism of pathogenesis is not fully explored (Cheon et al, 2019). Upregulation of Th17 cells and IL-17A responses in RSV infection are associated with increased neutrophil recruitment and pulmonary pathogenesis in infants as well as in BALB/c mouse model of RSV (Mukherjee et al, 2011).…”
Section: Influenza Virusmentioning
confidence: 99%
“…Other studies have shown that RSV G protein priming modulates eosinophil trafficking and function [130][131][132], and sublingual administration with the RSV G protein CCD primes mice for pulmonary eosinophilia and results in greater eosinophils compared to FI-RSV priming [133]. Sublingual priming was also shown to prime both pulmonary eosinophilia and neutrophilia in the lung tissue [134].…”
Section: Eosinophilsmentioning
confidence: 94%
“…Many vaccine prototypes are focused on viral surface proteins ( 36 , 37 ). One of the most common viral targets for antibodies is the RSV fusion (F) protein ( 38 , 39 ).…”
Section: Rsv Vaccine Modalities and Lessons From The Host Immune Respmentioning
confidence: 99%
“…The choice of administration route is an important decision in vaccine development, with most vaccines being delivered via the sublingual, intramuscular, or intranasal route. Sublingual administration of an RSV G protein vaccine induced enhanced cellular infiltration and pro-inflammatory cytokine production compared to intranasal delivery ( 37 ). Similar results were observed when a recombinant RSV attachment (G) protein containing the central regions for both RSV A and B serotypes was administrated either intranasally or sublingually ( 44 ).…”
Section: Rsv Vaccine Modalities and Lessons From The Host Immune Respmentioning
confidence: 99%
See 1 more Smart Citation